Feasting and Fasting - Katherine Gwyther (Old Testament Essays, 2021)
This article focuses on the feasting and fasting scenes that permeate the book of Esther. It examines the interactions between fasting and feasting through a lens of hybridity rather than reversal, as is the predominant approach of Western scholarship. To do so, it links the feasting and fasting to Persian and Jewish activity, respectively. Ultimately, it argues that Purim is an example of hybridity as it combines feasting and fasting in its observance, creating a hybrid of Persian and Jewish activity. The construction of Purim as a hybrid is considered in three sections and it relies on Homi K. Bhabha’s postcolonial conception of hybridity: (1) feasting and fasting as Persian and Jewish activity, (2) Esther’s mimicry and the beginning of the hybrid and (3) Purim as a hybrid. Understanding Purim as a hybrid, this article concludes by exploring how this hybrid can offer a challenge to the textual presentation of Persian hegemony in the book of Esther.